PENYELESAIAN SENGKETA TANAH BERDASARKAN HUKUM POSITIF TENTANG PENYELESAIAN SENGKETA DI INDONESIA - Tomson Situmeang; Poltak Siringoringo; I Dewa Ayu Widyani; L Elly AM Pandiangan; Putu George Matthew Simbolon; Hendri Jayadi (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM), Univesitas Kristen Indonesia, 2023)
The purpose of this article is to provide an understanding of land dispute resolutions available under Indonesian regulations. This article is applying the normative method under the statutory approach. Furthermore, the writer may provide the discussion of this article by expressing that there are two main classifications of land dispute resolution forums. The first forum known as the non-adjudication forum consists of mediation, conciliation, consultation, and facilitation. Meanwhile, the second forum is divided into two sub-classification consisting of the adjudication method and the non-adjudication method. The adjudication method consists of dispute settlement through a district court triggered by an ownership right dispute, and a dispute settlement through an administrative court regarding the legality of a land certificate. Besides that, the second sub-classification of this adjudication method consists of dispute settlement through arbitration that can be triggered due to an arbitration agreement with land as its object.